Coating techniques for biomaterials: A review - Chaijaruwanich A. (2017)
Biomaterials have been extensively studied for many decades. Surface modifications play a major role in determining the biological response. The purpose of this paper is to present an up-to-date progress in the coating techniques currently applied for biomaterials, including chemical treatment, anodic oxidation, micro-arc oxidation, sol-gel, plasma spray, electrostatic spray deposition, electrophoretic deposition and pulsed laser deposition. In the present paper, an overview of the basic principles behind the techniques is briefly given. A large number of research studies have shown a great thrust towards development of surface modification techniques for biomaterials. Coatings and films with nanostructures on bio-implants using various techniques have become a subject of interest.